A Systematic Review of Digital Da'wah Literacy Challenges in Islamic Communication - Muhammad Ahnu Idris (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2026)
This study explores the significance of digital literacy in enhancing contemporary da’wah practices across social media platforms amid the continuing evolution of digital communication technologies. The research seeks to investigate the extent to which digital literacy shapes the effectiveness, ethical dimensions, and continuity of Islamic communication within online media environments. Employing a Systematic Literature Review (SLR) design guided by PRISMA procedures, this study analyzed scholarly works published between 2020 and 2025 concerning digital da’wah, social media, and Islamic communication. A total of 35 academic references—including journal articles, books, theses, and dissertations indexed in Google Scholar, Garuda, Dimensions, Crossref, and Research Gate—were carefully selected and examined using content analysis methods. The findings demonstrate that digital literacy extends beyond technical proficiency and serves as a critical epistemological and ethical foundation influencing the credibility, authority, and communicative impact of digital da’wah. Furthermore, social media has shifted da’wah practices toward more participatory and algorithm-oriented forms of communication, requiring preachers to adopt adaptive strategies, critical media awareness, and context-sensitive religious narratives. The study also highlights several pressing challenges, including misinformation, the commodification of religious messages, and algorithmic bias, while simultaneously revealing broader opportunities for interactive Islamic learning and expanded public engagement. Ultimately, this research contributes to the field of contemporary Islamic communication by offering an integrated analytical perspective on the relationship between digital literacy, social media culture, and the transformation of da’wah in the digital era.